PRINSIP EFISIENSI DALAM PERADILAN TINDAK PIDANA PERIKANAN - sayidin abdullah (Fiat Justisia: Jurnal Ilmu Hukum, 2014)
This article seeks to examine the principle of efficiency in the execution of fisheries court. Based on the normative approach by using secondary data; can be concluded that the Fisheries Court is the Special Court in the scope of General Court that has an authority to examine, hear and decide criminal offenses of fisheries. Law on Fisheries is one of the cornerstones of a fundamental change in the law enforcement process of fisheries, through Fisheries Court by applying the principle of efficiency. Selection of efficiency principle is based on the simplicity to be understood, because it does not require the technical formulation of economics or figures. The focus of attention is regard to the possibility of emergence an inefficiency of the establishment, implementation and enforcement of legislation, namely the offenses fisheries, which includes investigation, prosecution, and examination against the criminal activities of fisheries in foreign fishing vessels which is doing an illegal fishing in the exclusive economic zone of Indonesia can be resolved by litigation that fulfill the principles of efficiency that is fast, accurate, and inexpensive. Keywords: Efficiency, Fisheries Court and Economic Law